Rhipicephalus microplus and Its Impact on Anaplasma marginale Multistrain Infections in Contrasting Epidemiological Contexts - Pérez, Agustina Ericlee; Guillemi, Eliana Carolina; Sarmiento, Nestor Fabian; Canton, German Jose; Farber, Marisa Diana (MDPI, 2025)
Bovine anaplasmosis is a disease caused by Anaplasma marginale, a tick-borne bacterial pathogen with global distribution, primarily determined by the range of its vector. In Argentina, Rhipicephalus microplus is the main species associated with A. marginale transmission, even though this bacterium can also be mechanically transmitted. We studied complex infections (more than one A. marginale variant) in naturally infected bovines from two different epidemiological contexts: a region with the tick vector and a tick-free region. In the tick-free area, symptomatic infections were associated with a single A. marginale genotype, while asymptomatic bovines from the same herd remained chronically infected with a low number of genotype variants. By contrast, in the region where R. microplus is present, the only symptomatic bovine showed highly diverse infections, with 19 distinctive genotypes. Additionally, A. marginale genotypes were also detected in tick tissues. These findings, together with previous data, indicate that R. microplus harbors A. marginale populations that are maintained through tick generations by means of transovarial transmission. Furthermore, this tick species is responsible for maintaining A. marginale diversity in the bovine host over time through coinfection and superinfection events